Early life stress in rats sex-dependently affects remote endocrine rather than behavioral consequences of adult exposure to contextual fear conditioning - Fuentes, Sílvia; Daviu, Núria; Gagliano, Humberto; Belda, Xavier; Armario, Antonio; Nadal, Roser (Hormones and behavior, 2018)
Exposure to electric foot-shocks can induce in rodents contextual fear conditioning, generalization of fear to other contexts and sensitization of the hypothalamic-pituitary-adrenal (HPA) axis to further stressors. All these aspects are relevant for the study of post-traumatic stress disorder. In the present work we evaluated in rats the sex differences and the role of early life stress (ELS) in fear memories, generalization and sensitization. During the first postnatal days subjects were exposed to restriction of nesting material along with exposure to a “substitute” mother. In the adulthood they were exposed to (i) a contextual fear conditioning to evaluate long-term memory and extinction and (ii) to a novel environment to study cognitive fear generalization and HPA axis heterotypic sensitization. ELS did not alter acquisition, expression or extinction of context fear conditioned behavior (freezing) in either sex, but reduced activity in novel environments only in males. Fear conditioning associated hypoactivity in novel environments (cognitive generalization) was greater in males than females but was not specifically affected by ELS. Although overall females showed greater basal and stress-induced levels of ACTH and corticosterone, an interaction between ELS, shock exposure and sex was found regarding HPA hormones. In males, ELS did not affect ACTH response in any situation, whereas in females, ELS reduced both shock-induced sensitization of ACTH and its conditioned response to the shock context. Also, shock-induced sensitization of corticosterone was only observed in males and ELS specifically reduced corticosterone response to stressors in males but not females. In conclusion, ELS seems to have only a minor impact on shock-induced behavioral conditioning, while affecting the unconditioned and conditioned responses of HPA hormones in a sex-dependent manner. •Long-term cognitive fear generalization was greater in males than females.•ELS did not affect cognitive fear generalization or conditioned freezing.•ELS induces a long-term decrease in exploration of novel environments only in males.•In females ELS reduced shock-induced ACTH sensitization and conditioned ACTH response.•ELS reduced corticosterone response to stressors in males but not females.